“Se te agarro com outro, te mato!”: reflexões sobre os crimes de feminicídio em João Pessoa-PB - Nascimento, Ana Amélia Dias Evangelista do (2020)
The main theme of the present work is feminicide as a social phenomenon. The general objective of the study is to analyze the concrete determinations of the crime of feminicide in Brazil, focusing on João Pessoa-PB, but for that it was necessary to contextualize the process of oppression and discrimination against women, being of utmost importance the discussion of the analytical category of Patriarchy, due to the fact that feminicide and other types of violence committed against women come from this category. In addition, we used statistical surveys on feminicide in the Brazilian and Paraíba context from Institutes such as the Map of Violence (2015), Women's Observatory Against Violence (2017), Economic Commission for Latin America and the Caribbean (2017), Brazilian Public Security Forum (2018-2019), United Nations Office on Drugs and Crime (2018), Atlas of Violence (2018-2019) and the Women's Center 8 de Março (2015-2018), a non-governmental organization that monitors crimes of violence against women through the written and online press, in the perspective of evidencing the increase in feminicide rates and indexes, and the particularities surrounding this violence. To this end, the methodology brings data referring to bibliographic research articulated to documentary and field research, focused on the collection and analysis of data from the legal records of feminicides deprived of freedom, between September and October 2018, who committed feminicide, even if not framed by the qualifying law in force (Law 13.140/2015) and serve sentences in closed regime in the penitentiaries Desembargador Sílvio Porto and Criminalista Geraldo Beltrão, both of maximum security, located in João Pessoa-PB. The researched subjects maintained or had maintained intimate and affective relations with the victims, were known or unknown to these women. The research was mixed, with qualitative and quantitative data and, as a method of analysis, the dialectic method, which provided us with reflection and critical knowledge about reality and its several specificities and contradictions, in the context of the concrete totality. Due to the high rates of extreme violence committed against women, in which Brazil ranked 5th among 83 countries in the world that kill the most women, it was enacted on March 9, 2015, by the then president Dilma Rousseff, the qualifying law of feminicide crimes (13.140/2015), qualifying as a heinous crime the murder of women as a result of domestic and family violence, and by contempt/discrimination for the condition of being a woman. Feminicide, like other forms of violence, is present in all social classes, but it appears more frequently in the working class, among black women, and has characteristics - such as the place of the crime, instruments, motivations and narratives - that distinguish it from the homicide committed against men.